Sexual intermingling of Arab and Jewish MSM in Israel: results of a molecular epidemiology study. (1st February 2019) - Zuckerman, Neta S.; Mor, Zohar; Bucris, Efrat; Wax, Marina; Mendelson, Ella; Mor, Orna
Abstract : Objectives: MSM comprise ∼30% of new HIV infections in Israel, a country with mixed Jewish and Arab populations. We molecularly characterized HIV-1 in the Arab and Jewish MSM (AMSM, JMSM) populations to reveal possible interethnical connections. Design: Cross-sectional study. Methods: All Israeli-born, HIV-1-infected MSM diagnosed between 2005 and 2016 ( n = 1143) were cross-matched with the National Civil Registry to identify religion (Jews/Muslims/Christians). Transmitted drug-resistance mutations (TDRM) and HIV-1 subtypes were determined on the first partial protease and reverse transcriptase sequences from treatment-naive patients and phylogenetic trees were constructed. Results: Among MSM, 6.4% (73/1143) were Arabs and 93.6% (1070/1143) were Jews. Interestingly, a higher proportion of Arabs was identified among non-MSM (19%, 46/247 versus 6.4%, 73/1143, P < 0.01). Subtype analysis of 62 HIV-1 AMSM and 440 randomly selected HIV-1 JMSM sequences revealed 80.6, 8.1, 4.8 and 6.5% of AMSM and 82.3, 9.5, 4.1 and 4.1% of JMSM had B, A, C and non-A/B/C, respectively. Overall, 13.1% (66/502) had TDRM; reverse transcriptase-K103N/S, M184 V, T215S and protease-L90M were the most common. TDRM prevalence was not significantly higher in JMSM compared to AMSM ( P = 0.1) and no temporal changes were observed in their frequency. Phylogenetic analysis demonstrated AMSM and JMSM clusters including L90M, K103N/S or T215S TDRM. Conclusion: Intermingling of AMSM and JMSM HIV-1 in clusters of HIV-1 sequences suggest interethnical sexual contacts among these MSM. Interventions aiming to prevent HIV-transmission in MSM should similarly address both populations groups. The high TDRM frequency requires continuation of resistance testing. Abstract : Supplemental Digital Content is available in the text